Analisis Struktur Pasar Pelayaran Akibat Konsolidasi dan Aliansi Global - Meryana Aisyah; Eliyanti A Mokodompit (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study analyzes how global consolidation and strategic alliances are reshaping the structure of Indonesia’s maritime shipping market. International environmental regulations particularly IMO 2023 and the Net-Zero 2050 target have intensified capital requirements for fleet modernization, driving mergers, acquisitions, and alliances as strategies to achieve economies of scale and improve competitiveness. Using a descriptive qualitative method and literature-based analysis, the research reviews scholarly journals, industry reports, and international maritime data. The findings show that while global consolidation enhances operational efficiency, route integration, and cost reduction, it also increases market concentration and entry barriers for smaller carriers. In Indonesia, despite its geostrategic position with 40% of global trade passing through its waters, foreign operators still dominate over 96% of international cargo transport. Government initiatives such as the Sea Toll Program and port modernization have improved connectivity, though structural challenges such as low shipyard productivity and high logistics costs continue to limit national competitiveness.The study concludes that consolidation is essential for strengthening Indonesia’s shipping capacity and competitiveness, but requires comprehensive policy support to enhance logistics efficiency and integrate national carriers into global networks.